A preliminary study on motivation and gender in CLIL and non-CLIL types of instruction - Fernández Fontecha, Almudena; Canga Alonso, Andrés (International Journal of English Studies, 2014)
This paper sets out to enquiry about gender-based differences in motivation towards EFL in two different types of instruction, i.e. CLIL and EFL (non-CLIL). The study was carried out with 4th Primary education Spanish students randomly selected from two mixed-gender schools in La Rioja (Spain). The results show that non-CLIL learners are significantly more motivated than CLIL learners. The non-CLIL girls are slightly more motivated than non-CLIL boys. However, CLIL boys are slightly more motivated than CLIL girls. Non-CLIL boys are more motivated than CLIL boys, and non-CLIL girls are more motivated than CLIL girls. These findings indicate that research on CLIL should closely take into account the way this methodological approach is implemented in a specific context since context-specific elements play a pivotal role in students’ motivation towards EFL. doi: http://dx.doi.org/10.6018/ijes/14/1/156681